PEMERIKSAAN BUTA WARNA, GOLONGAN DARAH DAN KADAR HEMOGLOBIN PADA ANAK USIA SEKOLAH DI NAGARI SUMANIAK - Aisyah Elliyanti; Dian Pertiwi; Arina Widya Murni; Zelly Dia Rofinda; Hendriati Hendriati; Julizar Julizar; Rahmat Syawqi; Husnil Wardiyah (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
The growth and development of children disturbance is a health problem that often is found in the community. Anemia and colour blindness are also health conditions that can affect the quality of growth and development of children, which parents rarely realize. The blood type of children is seldom defined in early ages by the parents. This activity aims to conduct health counselling, the examination of colour blindness, blood type, and hemoglobin levels in school-age children in Sumanik village. Methods: Activities were health education on how to wash hands properly and be aware of internet content. The activities were continued by a health examination, such as examining colour blindness, hemoglobin levels, and blood type. Testing of blood type on 76 children, two of 79 children has partial colour blindness. We found From 28 children (36.4%) having anemia, with hemoglobin levels 9.2-11.9 gr / dL, and one child has a blood type B rhesus (-). From this activity, it can be concluded that the low level of knowledge of school-age children in Kenagarian Sumaniak about how to wash hands properly and correctly, even children do not know the adverse effects associated with adult content on the internet. In addition, it appears that children with anemia are still relatively high. For this reason, continuous health promotion is needed. For disorders that can not be overcome at the time of activity, it is recommended to get treatment to the nearest health care centre.